Anthelmintic therapy in ruminant species: Understanding of the host-drug-parasite interaction - Lanusse, Carlos Edmundo (2010)
Inadequate use of anthelmitic drugs in livestock animals has led to therapeutic failures and to the dramatic widespread development of parasite resistance. Additional scientific knowledge on how to improve the use of available and novel molecules is required to avoid/delay resistance development. The time of parasite exposure to active drug concentrations determines the efficacy and/or persistence of activity for most of the anthelmintic drugs used in ruminants. The outcome from integrated pharmaco-parasitological research approaches addressed to interpret the host-drug-parasite relationship has greatly contributed to optimise drug activity. The integrated assessment of the drug disposition in the host, the mechanisms of drug influx/efflux in different target helminths, their biotransformation/detoxification capacities and the chemically-induced modulation of those transport/metabolism processes, has signified a relevant progress on the understanding of the pharmacology of anthelmintic drugs in ruminant species. Further pharmaco-parasitological interdisciplinary work, supported by the huge progress achieved on parasite genomics, will be essential to generate the basic scientific knowledge necessary to preserve existing and particularly, novel active ingredients as useful tools for parasite control in livestock animals. The basic and clinical pharmacology issues summarised in the current article contribute in that direction.